MR1 deficiency enhances IL-17-mediated allergic contact dermatitis - Imahashi, Naoya; Satoh, Masashi; Clemente, Emanuela; Yoshino, Kazuhisa; Di Gioacchino, Mario; Iwabuchi, Kazuya (Frontiers in Immunology, 2023)
Major histocompatibility complex (MHC) class Ib molecules present antigens to subsets of T cells primarily involved in host defense against pathogenic microbes and influence the development of immune-mediated diseases. The MHC class Ib molecule MHC-related protein 1 (MR1) functions as a platform to select MR1-restricted T cells, including mucosal-associated invariant T (MAIT) cells in the thymus, and presents ligands to them in the periphery. MAIT cells constitute an innate-like T-cell subset that recognizes microbial vitamin B2 metabolites and plays a defensive role against microbes. In this study, we investigated the function of MR1 in allergic contact dermatitis (ACD) by examining wild-type (WT) and MR1-deficient (MR1-/-) mice in which ACD was induced with 2,4-dinitrofluorobenzene (DNFB). MR1-/- mice exhibited exaggerated ACD lesions compared with WT mice. More neutrophils were recruited in the lesions in MR1-/- mice than in WT mice. WT mice contained fewer MAIT cells in their skin lesions following elicitation with DNFB, and MR1-/- mice lacking MAIT cells exhibited a significant increase in IL-17-producing αβ and γδ T cells in the skin. Collectively, MR1-/- mice displayed exacerbated ACD from an early phase with an enhanced type 3 immune response, although the precise mechanism of this enhancement remains elusive.